Transforming the Republic of Letters : Pierre-Daniel Huet and European Intellectual Life, 1650-1720 - Shelford, April (Book collections on Project MUSE., 2007)
Early modern Europe's most extensive commonwealth -- the Republic of Letters -- could not be found on any map. This republic had patriotic citizens, but no army; it had its own language, but no frontiers. From its birth during the Renaissance, the Republi.